PJE The Impact and Efficiency of Electronic Libraries in Various Districts of Punjab, Pakistan - Ehsan Bhutta,Yasir Rasool, Chaudhary Abdul Rehman, (PJE, 2023)
The present research study was conducted with the aim to assess and analyze the impact of electronic libraries (EL) by using usability criteria which include consistency, efficiency, learning and satisfaction in digital learning and reading stimulus among the general public and youth in specific. The structural equation modeling (SEM) of variables like effectiveness (EEF), efficiency (EFT), learning ability (LER) and performance & satisfaction (PES) was followed by research design.